Synchronous behavioural shifts in reef fishes linked to mass coral bleaching. Issue 11 (November 2018) - Keith, Sally; Baird, Andrew; Hobbs, Jean-Paul; Woolsey, Erika; Hoey, Andrew; Fadli, N.; Sanders, Nathan
Abstract Mass coral bleaching causes population declines and mortality of coral reef species1 yet its impacts on behaviour are largely unknown. Here, we unite behavioural theory with community ecology to test whether bleaching-induced mass mortality of corals can cause consistent changes in the behaviour of coral-feeding fishes. We documented 5, 259 encounters between individuals of 38Chaetodon (butterflyfish) species on 17 reefs within the central Indo-Pacific, of which 3, 828 were repeated on 10 reefs both before and after the global coral bleaching event in 2016. Aggression between butterflyfishes decreased by two-thirds following large-scale coral mortality, despite no significant change in fish abundance or community composition. Pairwise encounters were most likely to be aggressive between obligate corallivores and on reefs with high coral cover. After bleaching, the proportion of preferredAcropora corals in the diet decreased significantly (up to 85% fewer bites), with no increase in overall bite rate to compensate for the loss of these nutritionally rich corals. The observed reduced aggression at low resource levels due to nutritional deficit follows the predictions of the economic theory of aggressive behaviour2, 3 . Our results reveal synchronous changes in behaviour in response to coral mortality. Such changes could potentially disrupt territories4, leading to reorganization of ecological communities. The impact of coral bleaching and mortality is found to reduce aggression in resident butterflyfish. This is linked to the lower dietary percentage of preferred food, nutritionally richAcropora coral, with a less nutritious diet influencing aggressive behaviour.